Acquiring Competencies in Financial Translation: From the Classroom to the Marketplace - Román Mínguez, Verónica (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2012)
Translating financial texts is a difficult and complex work. The labour market in this specialized area demands much of the translator, not only from the point of view of the translation subject matter itself, but also from the perspective of the translator’s professionalism and preparedness. Our contribution here concerns applied research for teaching specialized translation, particularly for the teaching-learning process regarding financial translation for the language pair English-Spanish. This article will discuss the different translation sub-competencies that we propose students should master, offering a series of teaching-learning objectives and suggesting the use of certain pedagogical material. With respect to professional sub-competencies, and in order to make translation learning experiences in the classroom as close as possible to the actual practice of translation in the real world, i.e. in a professional working environment, we will discuss certain characteristics of the professional labour market in the area of financial translation, as well as some of the professional skills that the student translators should develop in order to survive in this specialized domain of translation.